Improving the flexibility and compostability of starch/poly(butylene cyclohexanedicarboxylate)-based blends. (15th October 2020) - Dominici, Franco; Gigli, Matteo; Armentano, Ilaria; Genovese, Laura; Luzi, Francesca; Torre, Luigi; Munari, Andrea; Lotti, Nadia
Highlights: Blends of TPS and poly(butylene cyclohexanedicarboxylate- co -adipate) are prepared. Adipic acid co-units decrease melt blending temperature to avoid TPS degradation. Citric acid, used as compatibilizing agent, improves interfacial adhesion. Films show high flexibility, good moisture resistance and fast compost fragmentation. Abstract: Fully biobased blends of thermoplastic starch and a poly(butylene cyclohexanedicarboxylate)-based random copolyester containing 25 % of adipic acid co-units (PBCEA) are prepared by melt blending and direct extrusion film casting. The obtained films are characterized from the physicochemical and mechanical point of view and their fragmentation under composting conditions is evaluated. The results demonstrate that the introduction of adipic acid co-units in the PBCE macromolecular chains permits to decrease the blending temperature, thus avoiding unwanted starch degradation reactions. Moreover, the presence of small amounts of citric acid as compatibilizer further improves the interfacial adhesion between the two components and promotes the formation of micro-porosities within the films. The synergistic combination of these factors leads to the development of materials showing an elastomeric behavior, i.e. no evident yield and elongation at break higher than 450 %, good moisture resistance and fast fragmentation in compost.